MR-lymphangiography at 3.0 T--a feasibility study. - Notohamiprodjo M; Baumeister RG; Jakobs TF; Bauner KU; Boehm HF; Horng A; Reiser MF; Glaser C; Herrmann KA; Notohamiprodjo, Mike; Baumeister, Ruediger G H; Jakobs, Tobias F; et al. (European Radiology, 2009)
The purpose of this study was to establish and evaluate contrast-enhanced MR-lymphangiography (MRL) at 3.0 T for detection and visualization of abnormalities of the peripheral lymphatic system. Sixteen patients were examined with a highly resolved isotropic T1w-3D-GRE-(FLASH) sequence (TR 3.76 ms/TE 1.45 ms/FA 30 degrees /voxel-size 0.8 x 0.8 x 0.8 mm(3)) at 3T after intracutaneous injection of gadolinium-diethylene-triamine-pentaacetic-acid. Two radiologists evaluated overall image quality, contrast between lymph vessels and background tissue, venous contamination, visualized levels, and fat-saturation-homogeneity on 3D maximum-intensity projections. Overall image quality was good to excellent, and all examinations were diagnostic except one, where contrast medium was injected subcutaneously instead of intracutaneously. Overall image quality was good to excellent in 12/16 cases, depiction of lymph vessels was good to excellent in 15/16 cases. Venous contamination was always present, but diagnostically problematical in only one case. Instant lymphatic drainage was observed in unaffected extremities, reaching the pelvic level after approximately 10 min. Lymphatic drainage was considerably delayed in lymphedematous extremities. Ectatic lymph vessels, entrapment, and diffuse drainage of contrast medium correlated with impaired lymphatic drainage. In conclusion, MRL at 3.0 T provides very high spatial resolution and anatomical detail of normal and abnormal peripheral lymph vessels. MRL may thus become a valuable tool for microsurgical treatment planning and monitoring.